PERBEDAAN HASIL BELAJAR SISWA MENGGUNAKAN MODEL PEMBELAJARAN KOOPERATIF TIPE PAIR CHECK DENGAN TIPE THINK PAIR SQUARE DI SMA - Nurul Huda Arianti; Syubhan Annur; Mastuang Mastuang (Universitas Lambung Mangkurat, 2017)
Student learning outcomes is still less than optimal or unsatisfactory, it can be known through the data replication midterm class XI IPA at SMAN 9 Banjarmasin. This happens because the learning methods and models used by teachers based on observations during the learning tend to be monotonous and less engaging students, so that students are less enthusiastic and less active in the following study. This study aims to determine whether there are differences in learning outcomes of students using cooperative learning model Pair Check with the type of Think Pair Square in class XI SMA Negeri 9 Banjarmasin. This type of research used in this research is quantitative quasi-experimental research design. This study population is all students in grade XI IPA at SMAN 9 Banjarmasin. Samples were taken using cluster random sampling. Data collection techniques are techniques achievement test and documentation. The results showed that there are differences in learning outcomes of students using cooperative learning model Pair Check with the type of Think Pair Square in class XI SMA Negeri 9 Banjarmasin.